Kosovo Country Economic Memorandum, November 2021 : Enhancing Human Capital by Improving Education - World Bank (World Bank, Washington, DC, 2022)
This note assesses pre-university education in Kosovo and identifies policies that can improve education quality and equity. There is a substantial need for improvement to the foundations of the education system, especially in terms of coverage and quality. If Kosovo is to reap the benefits of its demographic dividend for faster growth and poverty reduction, making it a policy to invest in human capital through education must be a priority. The low levels of foundational literacy skills limit the ability of Kosovars to develop the skills the labor market requires, especially for those living in rural areas and minority communities and those of low socioeconomic status. Kosovo has made considerable progress in increasing access to preprimary and primary education, but more needs to be done to equitably increase coverage of preschool and secondary education. Narrowing the wide geographic, ethnic, and socioeconomic disparities in education outcomes and ensuring that all children have access to quality education is paramount. The Coronavirus disease 2019 (COVID-19) pandemic is expected to further erode Kosovo’s modest improvements made in education. Employers in Kosovo note the poor quality of the education system and the limited practical and professional skills students acquire.